Exploiting sweetpotato as an animal feed in East Africa - International Potato Center (2013)
Sweetpotato o!ers great potential as an animal feed in sub-Saharan Africa (SSA) but its potential use as a feed or dual purpose (food and feed) crop has not been fully exploited. Dry season feed shortage has long been a problem in many parts of SSA. Researchers have developed an improved silage tube and tested the resultant sweetpotato silage on growing pigs with small-scale farmers in Kenya.